Evaluasi Pembelajaran Mapel Fiqih Bagi Anak Berkebutuhan Khusus di MTs Wachid Hasyim Surabaya - Anshar, Muhammad; Ismail, Ismail; Zakariyah, Anik; Syahrul Alim, Adam Ahmad (Belajea: Jurnal Pendidikan Islam, 2020)
This research is motivated by the problem of children with special needs in inclusive schools. This study aims to reveal the process to the evaluation report using the ABK CPIP (Context, Input, Process, Product) model. Whereas the subject to be discussed is to focus on the subject of fiqh as one of the subjects of PAI that is applied at MTs Wahid Hasyim Surabaya. The object of this study is the principal, ABK assistant teachers, and the inclusive class coordinator, accompanied by data in the field that can support this research. The results of this study conclude that the evaluation of learning with the CIPP model provides optimal supervision between subject teachers and ABK companion teachers for mastery of material for children with special needs, ranging from planning, learning processes, evaluations and products, so that ABK does not miss lessons with special attention through the process of achieving learning objectives